Tailoring high-performance bipolar membrane for durable pure water electrolysis - Weisheng Yu; Zirui Zhang; Fen Luo; Xiaojiang Li; Fanglin Duan; Yan Xu; Zhiru Liu; Xian Liang; Yaoming Wang; Liang Wu; Tongwen Xu (Nature Communications)
Abstract Bipolar membrane electrolyzers present an attractive scenario for concurrently optimizing the pH environment required for paired electrode reactions. However, the practicalization of bipolar membranes for water electrolysis has been hindered by their sluggish water dissociation kinetics, poor mass transport, and insufficient interface durability. This study starts with numerical simulations and discloses the limiting factors of monopolar membrane layer engineering. On this foundation, we tailor flexible bipolar membranes (10 ∼ 40 µm) comprising anion and cation exchange layers with an identical poly(terphenyl alkylene) polymeric skeleton. Rapid mass transfer properties and high compatibility of the monopolar membrane layers endow the bipolar membrane with appreciable water dissociation efficiency and long-term stability. Incorporating the bipolar membrane into a flow-cell electrolyzer enables an ampere-level pure water electrolysis with a total voltage of 2.68 V at 1000 mA cm–2, increasing the energy efficiency to twice that of the state-of-the-art commercial BPM. Furthermore, the bipolar membrane realizes a durability of 1000 h at high current densities of 300 ∼ 500 mA cm–2 with negligible performance decay.